The incident of the five kidnapper’s in1956 through the memoirs of Ahmed Ben Bella (Critical analytical study) - bourezg, Warda; SADAOUI, Mustapha (The Algerian Historical Journal, 2026)
Personal memoirs are a fundamental source of information documented by numerous politicians, writers, historians, mujahedeen, and media professionals who either witnessed or took part in the event. Each of them described the event in his own unique style, recording his observations and the human situations he saw or lived. Personal memoirs are one of the most crucial historical writing sources to understand the formation of Algerian collective consciousness. In order to determine the historical truth, methodological guidelines must be carefully and deliberately followed, beginning with the attentive reading, analysis, and synthesis of events by the researcher. Only the researcher must be competent to judge their veracity and objectivity. In this study, we chose to exploit the testimony of Ahmed Ben Bella about the Moroccan plane hijacking in 1956, carrying the five leaders of the Algerian revolution travelling from Rabat to Tunis to participate in the Maghreb conference. This pivotal moment was an important part of what transpired during our glorious revolution, of which Ben Bella was one of its victims. Additionally, in order to reveal the truth that implicates France and supports our demand that it be held accountable as a first-degree war criminal, we seek to examine this testimony objectively and critically.